2009
DOI: 10.1086/605959
|View full text |Cite
|
Sign up to set email alerts
|

Unifying Wildfire Models from Ecology and Statistical Physics

Abstract: Ecosystems display a complex spatial organization. Ecologists have long tried to characterize them by looking at how different measures of biodiversity change across spatial scales. Ecological neutral theory has provided simple predictions accounting for general empirical patterns in communities of competing species. However, while neutral theory in well-mixed ecosystems is mathematically well understood, spatial models still present several open problems, limiting the quantitative understanding of spatial bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(29 citation statements)
references
References 41 publications
1
28
0
Order By: Relevance
“…Clear-cut partitioning of bottom-up vs. topdown controls is difficult (Peters et al 2004, Zinck andGrimm 2009), in part because bottomup factors usually interact amongst themselves, as well as with top-down controls (Gavin et al 2006, Parisien et al 2010. Simulation modeling provided the means, through input manipulation, to isolate the effect of bottom-up environmental factors on spatial fire likelihood in four fire-prone landscapes of North America.…”
Section: Resultsmentioning
confidence: 99%
“…Clear-cut partitioning of bottom-up vs. topdown controls is difficult (Peters et al 2004, Zinck andGrimm 2009), in part because bottomup factors usually interact amongst themselves, as well as with top-down controls (Gavin et al 2006, Parisien et al 2010. Simulation modeling provided the means, through input manipulation, to isolate the effect of bottom-up environmental factors on spatial fire likelihood in four fire-prone landscapes of North America.…”
Section: Resultsmentioning
confidence: 99%
“…Zinck & Grimm showed that these two additional patterns are also produced by the physicists' model if grid cells represent entire tree stands of several hectares instead of individual trees [35,44]. They also showed that the key process for reproducing all three patterns is a 'memory effect': flammability increases with the time since a site last burned.…”
Section: Examplesmentioning
confidence: 97%
“…Depending on the scenario intraspecific negative density regulation of seedlings is considered in the seed dispersal and seed production sub-model. Fire occurs every year (one ignition per year) somewhere on the 144-km 2 grid, the ignition location (cell) is chosen at random and the fire's spatial structure is determined by a percolation model [29], [30]. Not all fires spread across the metacommunity simulation arena containing the habitat patches.…”
Section: Methodsmentioning
confidence: 99%